Anatomical Perspective of Basti Marma in Ayurveda with Special Reference to Its Clinical Significance in Urological and Pelvic Disorders - Kumar, Mahesh; Priyanka, Priyanka; Gupta, S. S. (Journal of Neonatal Surgery, 2025)
Ayurveda identifies Marma points as vital anatomical locations where injury can result in severe physiological dysfunction or even mortality. Among these, Basti Marma, situated in the pelvic region, holds critical importance due to its association with the urinary bladder and reproductive organs. Classical Ayurvedic texts describe Basti Marma as a key site influencing urinary and reproductive health, emphasizing its vulnerability and the severe consequences of trauma or imbalance at this site. This review aims to integrate the traditional Ayurvedic understanding of Basti Marma with contemporary anatomical knowledge of the urinary bladder and surrounding pelvic structures. Modern anatomy elucidates the complex muscular, neurovascular, and ligamentous framework supporting the bladder and maintaining pelvic organ function, which parallels the Ayurvedic depiction of Basti Marma as a composite of muscles, vessels, ligaments, and bone. The clinical significance of this region is highlighted through discussions of urological and pelvic disorders such as urinary retention, incontinence, cystitis, pelvic trauma, and neurogenic bladder dysfunction. This comprehensive perspective underscores the potential of combining Ayurvedic marma therapy with modern diagnostic and rehabilitative approaches to improve patient outcomes in pelvic and urinary conditions. A better understanding of Basti Marma facilitates holistic and integrative management strategies that respect both traditional wisdom and biomedical science, paving the way for enhanced therapeutic modalities in urology and pelvic health.